META-ANALISIS PENGGUNAAN VIDEO PEMBELAJARAN PADA MASA PANDEMI COVID-19 TERHADAP HASIL BELAJAR FISIKA PESERTA DIDIK - Antikha AK, Dirwanti July; Tandililing, Edy; Hidayat, Muhammad Musa Syarif (Universitas Tanjungpura, 2023)
The Changes of community conditions during the Covid-19 Pandemic have forced us to implement a distance learning system by online. This study aimed to find the effect of using learning videos during the Covid-19 pandemic on student learning outcomes through a meta-analysis of national research journals. The influence was reviewed bycalculating the average effect size of the selected research journals and analyzing the variables that affect the effect size. The form of research in this study is documentation, whic are collecting and summarizing documents in the form of national-scale research journals. Based on the results of calculations using the comparison formula of Glass and its derivatives, an average effect size of 0.52 from 10 journal articles was produced on the effect of using learning videos on learning outcomes. The effect size is in the medium category and shows that the use of learning videos during the Covid-19 pandemic is quite effective in the online learning process